Improved performance of InSe field-effect transistors by channel encapsulation - Liang, Guangda; Wang, Yiming; Han, Lin; Yang, Zai-xing; Xin, Qian; Kudrynskyi, Zakhar R.; Kovalyuk, Zakhar D.; Patanè, Amalia; Song, Aimin (IOP Publishing, 2018)
Due to the high electron mobility and photo-responsivity, InSe is considered as an excellent candidate for next generation electronics and optoelectronics. In particular, in contrast to many high-mobility two-dimensional (2D) materials, such as phosphorene, InSe is more resilient to oxidation in air. Nevertheless, its implementation in future applications requires encapsulation techniques to prevent the adsorption of gas molecules on its surface. In this work, we use a common lithography resist, poly (methyl methacrylate) (PMMA) to encapsulate InSe-based field-effect transistors (FETs). The encapsulation of InSe by PMMA improves the electrical stability of the FETs under a gate bias stress, and increases both the drain current and electron mobility. These findings indicate the effectiveness of the PMMA encapsulation method, which could be applied to other 2D materials.